Analisis Sistem Pengembangan Pemasaran Jambu Biji di Desa Perawang Barat Kecamatan Tualang Kabupaten Siak Provinsi Riau - Saputra, Deni Ilham; Dewi, Ilma Satriana (UIR PRESS, 2026)
Tualang is one of the sub-districts in Siak Regency that produces the largest guava fruit in 2023. Research objectives: (1) Analyzing the characteristics of guava farmers and traders, (2) Analyzing marketing which includes institutions, channels, functions, costs, margins, profits, efficiency and Farmer's Share of guava, (3) Analyzing guava marketing development strategies. The method used is the survey method. Determination of the research location was carried out deliberately in Perawang Barat Village, Tualang District, Siak Regency. The samples in this study were 31 farmers, 6 collectors and 4 retailers. The results of the study are the majority of farmers have elementary school education (46.67%), collectors of high school (66.67%), and retailers of junior high school (50%). The dominant business experience of farmers is 7-10 years, collectors 9-10 years, and retailers 9-12 years. The average family dependency is 3-4 people. There are three marketing channels: Farmer-middleman-consumer, Farmer-retailer-consumer, Farmer direct to consumer. Channel II is more efficient (2.7%) than channel I (3.5%). Farmer's Share is highest in channel III (100%). SWOT shows SO strategies: utilizing online media, highlighting guava quality, and affordable prices to improve marketing.